The role of religion in legends about Turkish attacks - Mlakar, Anja (Acta Histriae, 2021)
An analysis of Slovenian legends about Turkish raids was made to identify and analyze religious elements in them. The legends express superiority of Christianity, but also contain belief elements that diverge from Christian teachings, such as traditional Slavic beliefs about the afterlife. The mixture of different beliefs can summarized under the term “vernacular religion”. The Turks in folklore represented an archetypal demonic “Other” and as such they threaten the “Our” world. In these legends traditional and pre-Christian beliefs were intermixed with Christian symbolism and characters and as such they express the diversity and flexibility of religious imagery.
Keywords: čudeži; drugost; krščanstvo; onostranstvo; sveti prostor; svetoskrunstvo; turški vpadi; vernakularna religija